PENGARUH WORK LIFE BALANCE TERHADAP KEPUASAN KERJA YANG DIMEDIASI BURNOUT PADA DRIVER PT. GOJEK INDONESIA - Fadlan Fauzi; Muhamad Ekhsan (Universitas Muhammadiyah Tangerang, 2023)
The purpose of this study was to determine whether there is an effect of Work Life Balance on Job Satisfaction mediated by Burnout. The object of research at driver PT.gojek Indonesia This research was conducted using quantitative methods with SEM Smart PLS software as an analytical tool. The number of samples obtained by random sampling technique using the Hair et.al formula amounted to 77 respondents. Data collection is done through google from filling out questionnaires. The data analysis method used is the R-square test, Bootstrapping, Path Coefficient and Specific Indirect Effects. The results of this study indicate that Work Life Balance has a significant effect on Job Satisfaction, Work Life Balance has a significant effect on Burnout, Burnout has no significant effect on Job Satisfaction, besides that, it is also known that the Burnout variable can mediate the relationship between Work Life Balance and Job Satisfaction.